EMBEDDED PRESENTER TRACKING SYSTEM - MUSA, FAIZ SYAUQI (2018)
This paper presents the design and implementation of face detection mechanism by using Viola-Jones algorithm together with an actuator to track the movement of a presenter in front of a camera within the limit of x-axis or horizontal space plane. The objective of this project is to maintain the position of the presenter at the center of the video frame output by tracking the presenter’s location, in addition to improving previous prototypes to create a better and smoother tracking mechanism. A webcam is used for the prototype to provide visual input for the system before the Viola-Jones algorithm is used to detect the presence of a human face within the video frame input. The detected face area will be mapped and framed by a square or rectangle border in order to calculate the center face coordinates. The center coordinates of the face are then compared to the center coordinates of the screen and the required signals are transmitted to the Arduino microcontroller to control the movement of the servo motor that will maintain the center face position in the video output. Overall, the prototype can be operated and its tracking mechanism is better than previous prototypes as it has successfully executed real-time tracking system. However, there are various improvements that need to be done in order to make the tracking system mechanism to be usable within the industry standard quality.